The Islamic Perspective of Economic Development: The Challenges in Nigeria - Yisa Olorunda Balogun (The Eastasouth Journal of Social Science and Humanities, 2026)
Economic development is a very important factor in any given society. The onerous of the development lies on government and individual scholars, both within and outside a given country. The evaluation of economic development enables the government to know the position of the economy of a given country. This assists in finding means of improving the economy; guide on policy formulation, fostering accountability, transparency, sustainable growth and development. It guides the country on how to improve on her Gross Domestic Product (GDP). The paper examines the concept of economic development, characteristics of economic development such as increment in national income, improved standard of living and structural transformation. It discusses the significance of economic alleviation of poverty through Zakat, Mirat and Ajo Adako (periodic thrift). Different economic developmental challenges in Nigeria like poverty, politics, and tribalism were also discussed. Our recommendations include eradication of corruption, stabilization of democratic system and avoidance of religious biased, most especially in Nigerian politics.